Geochronology, Petrogenesis, and Tectonic Setting of the Late Triassic Banpo Pluton from the Western Part of the North Qinling Orogenic Belt - Li, Shuqin; Li, Zuochen; Pei, Xianzhi; Lin, Hao; Qin, Li; Ji, Shang; Yang, Yajie; Ren, Jinghong (Minerals (Basel), 2024)
Precise determination of the tectonothermal events at the Qinling–Qilian junction is significant for understanding the tectonic evolution of the eastern branch of the Paleo-Tethys. The Banpo pluton outcrops in the northern margin of the North Qinling were chosen as the research subject and their formation and tectonic environment were investigated using zircon U-Pb age and geochemical compositions. The weighted average values of 206Pb/238U ages of samples from three sites of the Banpo pluton corresponded to 213.4 ± 2.1 Ma (MSWD = 0.56), 213.0 ± 1.6 Ma (MSWD = 0.92), and 216.3 ± 2.3 Ma (MSWD = 2.0). All the samples are rich in light rare earth elements, exhibiting a seagull-type right-leaning partitioning curve, with obviously negative Eu anomalies. In addition, based on the regional geological data, it can be concluded that the Banpo pluton was formed during the transition period from a post-Orogenic environment to an anorogenic environment. The results indicated the final stage of the Triassic orogeny and the closure phase of the Paleo-Tethys. Also, it shows closure of the Paleo-Tethys-Mianxian-Lueyang Ocean by the Late Triassic period as well as the completion of the collision between the North China and Yangtze Blocks along the Qinling Orogenic Belt.